The effectiveness of interactive learning media on dance dynamics material using articulate storyline 3 in elementary schools - Cicilia Ika Rahayu Nita; Alfina Dela Wati (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Media in the learning process is an important component as a delivery of material, so that media must be packaged creatively and follow the development of the times. However, in reality, teachers have not utilized technological advances optimally in utilizing learning media in the classroom. The objectives of this study are 1) to develop learning media based on the articulate storyline 3 application on the content of art and culture lessons, 2) to describe the feasibility of learning media based on the articulate storyline 3 application on the content of art and culture lessons, 3) to describe the practicality of learning media based on the articulate storyline 3 application on the content of art and culture lessons, 4) to describe the effectiveness of learning media based on the articulate storyline 3 application on the content of art and culture lessons. The development research method uses the ADDIE development model using five stages, namely: analysis, design, development, implementation and evaluation. The subjects of this study were grade III students of SDN Tegalrejo 01. Data collection instruments used questionnaires, test questions, observations and interviews. The results of the study showed that the study had gone through 5 stages, namely analysis, design, development, implementation and evaluation. Based on the results of the study on the feasibility of learning media based on the articulate storyline 3 application on the content of SBdP lessons, it obtained an assessment from media experts of 96.67%, an assessment from material experts of 94% and an assessment from language experts of 90%. The results of practicality obtained from teacher assessments were 90.9% and student assessments were 91.28%. The results of effectiveness were obtained from pretest and posttest assessments. The pretest assessment obtained a percentage of 52 and the posttest assessment obtained a percentage of 94. Based on the results of these assessments, the learning media was considered feasible, practical, and effective to be used as learning media in the classroom.